Synthesis of poly(arylene ether nitrile) and carboxyl-functionalized poly(arylene ether nitrile) with high thermal stability and their thermal decomposition kinetics. (September 2019) - Wang, Huagao; Tang, Hailong; Yang, Junyi; Li, Youbing
Poly(arylene ether nitrile)s (PAENs) play an important role in special engineering materials owing to their excellent mechanical strength and superior thermal stability. In this study, PAEN and carboxyl-functionalized poly(arylene ether nitrile) (CPAEN) were successfully synthesized and their thermal parameters were determined through thermogravimetric analysis and differential scanning calorimetry to investigate the thermal decomposition kinetics and thermal stability. The results indicate that both PAEN and CPAEN exhibited high glass transition temperature and initial decomposition temperature. Meanwhile, the effects of the side groups on the thermal stability and the decomposition kinetic parameters of PAEN and CPAEN under nitrogen were discussed systematically. The kinetic parameters of PAEN and CPAEN were determined using the Kissinger and Ozawa methods, respectively. It reveals that the activation energy ( E ) values of PAEN obtained using the Kissinger and Ozawa methods were 192.45 and 206.63 kJ/mol, and the corresponding E values of CPAEN were 161.20 and 162.72 kJ/mol, respectively. The thermal decomposition mechanism of PAEN and CPAEN obtained from Coats–Redfern methods goes for F 3 and D 1 models, respectively.